The human experimentation of new drugs: research on the consent of the subject - Rodriguez, Daniele; Meloni, Lorenzo; Lavagnolo, Cinzia (Medicina e Morale, 1991)
One important question concerning the human experimentation of new medicines is the consent of the person subjected to the experimentation. In particular there is the question of consent in the human experimentation of new drugs in the psychiatric sphere. With reference to this argument, in this article we reported and discussed the data deduced from the analysis of the experimental publications included in Italian psychiatric journals and then we compared these results with the results from our previous research.